Efektivitas Model Pembelajaran Questioning, Organizing, Doing, And Evaluating (QODE) untuk Pembelajaran IPA di SMP - Retno Irawati; Sutarto Sutarto; Yushardi Yushardi (Jurnal Pembelajaran dan Pendidikan Sains, 2017)
This research is a research of development of QODE learning model (Questioning, organizing, Doing, and Evaluating) to study the effectiveness of QODE learning model for science lesson in junior high school. This research uses Action research model. The subject of this research is the students of SMP class VII in SMP Negeri 1 Dringu. Data collection technique used is a test of pretest and postes.yang analyzed by technique of normalized gain data analysis. The result of this research is to test the effectiveness of QODE learning model by using Normalized gain (g) data on student learning outcomes in cycle 1 that is -0.57 with low category and in cycle 2 (g) 0.50 with medium category. So the QODE learning model is effective in improving learning outcomes in each science lesson in low and medium category. Keywords: QODE learning model, effectiveness, science lesson